2020
DOI: 10.1177/0022243719892594
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancing Versus Backfiring Effects of Positive Emotion in Consumer Reviews

Abstract: Researchers, marketers, and consumers often believe that amplifying emotional content is impactful for the spread of information and purchasing decisions. However, there is little systematic investigation of when emotionality backfires. This research demonstrates when and why positive emotion can have enhancing versus backfiring effects. The authors find that reviewers who express greater positive emotion are indeed more positive toward their products, regardless of product type. In addition, expressed emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 76 publications
2
47
0
2
Order By: Relevance
“…Research by Hamilton, Vohs, and McGill (2014) found that the use of dispreferred markers as a means of softening the negative information featured in reviews (“I’ll be honest…”) led to higher willingness to pay for products because this makes reviewers appear more credible and likable. Finally, work by Rocklage and Fazio (2020) finds that effusive positive emotionality can increase evaluations for hedonic products but lower evaluations for utilitarian products. Previous research has also identified attributional elements in reviews that can positively or negatively affect the interpretation of the review by consumers, such as changing the focus from dispositional drivers to external causes of the reviewers’ behavior (Chen and Lurie 2013; Kupor and Tormala 2018; Mizerski 1982).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Hamilton, Vohs, and McGill (2014) found that the use of dispreferred markers as a means of softening the negative information featured in reviews (“I’ll be honest…”) led to higher willingness to pay for products because this makes reviewers appear more credible and likable. Finally, work by Rocklage and Fazio (2020) finds that effusive positive emotionality can increase evaluations for hedonic products but lower evaluations for utilitarian products. Previous research has also identified attributional elements in reviews that can positively or negatively affect the interpretation of the review by consumers, such as changing the focus from dispositional drivers to external causes of the reviewers’ behavior (Chen and Lurie 2013; Kupor and Tormala 2018; Mizerski 1982).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…First, while the majority of WOM research finds that negative reviews lead to negative consumer responses, we highlight a novel boundary condition for this effect—the degree to which the review is seen to be unfair. In doing so, we build on an emerging body of work documenting that the cues within the review content can influence consumer responses (Chen and Lurie 2013; Hamilton, Vohs, and McGill 2014; Rocklage and Fazio 2020). We find that, in addition to elements that enhance the credibility of the review (e.g., temporal cues, dispreferred markers, deviatory reviews, emotionality), perceived unfairness in reviews can enhance empathy, motivating subsequent helping and positive intentions toward the firm.…”
mentioning
confidence: 99%
“…Product category moderates this effect: greater emotionality has a positive impact on helpfulness ratings and product evaluations for hedonic purchases, but a negative impact for utilitarian purchases. This occurs because senders who use consistent, expected language (i.e., emotional language for hedonic products) produce a positive player signal about themselves and are therefore perceived as more trustworthy (Rocklage & Fazio, ).…”
Section: Sendermentioning
confidence: 99%
“…Second, we aimed to examine a behavioral outcome that potentially results from decreased happiness with purchases: less positive (more negative) consumer reviews. Recent work shows that people who are more positive about a purchase express more positive emotions in their reviews (Rocklage and Fazio 2020). Therefore, if financially constrained consumers derive less happiness from their purchases, they should also write less positive reviews for their purchases.…”
Section: Study 2: Consumer Reviewsmentioning
confidence: 99%